Trisomy 14 as the only cytogenetic abnormality in myelodysplastic syndrome - M. N. Pautova; L. E. Koloskova; O. I. Filippova; A. V. Koloskov (Онкогематология)
Evaluation of bone marrow cytogenetic abnormalities in myelodysplastic syndrome is of great importance for confirming the clonal disease nature, determining the prognosis and choosing treatment tactics. Cytogenetic abnormalities are detected in 40–70 % of patients with myelodysplastic syndrome, and the variety of these abnormalities reflects the disease characteristics.This article describes the clinical follow-up of a patient with a myelodysplastic neoplasia with blast excess 1 and trisomy of chromosome 14.